About the concept of universality in International Criminal Law - Mattos Rázuri, Sergio (2022)
Throughout this article, the author will seek to prove that the concept of universality —which serves as a basis for the universal criminalization of particular acts— is nothing more than a fiction that does not respond to the noblest of reasons. He will build his analysis on the basis of the narratives of humanity and its atrocity, then analyze the concept of universality as a generally accepted attribute in international law and examine the discussion that exists with respect to natural law and positivism. Finally, it will provide a constructive critique of the concept, establishing the logic, strengths and inconsistencies behind the humanity and atrocity narratives of universality in international criminal law.